Odpowiedź :
zad1 x = -20
4³ = 4-3x
64 = 4-3x
60 = -3x
-20 = x
zad2 x > 4,5
2³ < 2x-1
8 < 2x-1
9 <2x
4,5 < x
4³ = 4-3x
64 = 4-3x
60 = -3x
-20 = x
zad2 x > 4,5
2³ < 2x-1
8 < 2x-1
9 <2x
4,5 < x
zad1 log4(4-3x)=3 zał. 4-3x>0→-3x>-4→x<4/3
4-3x=4³
-3x=64-4
-3x=60
x=-60/3
x=-20
zad2 log2(2x-1)<3 zał: 2x-1>0→2x>1→x>1/2
2x-1<2³
2x<8+1
2x<9
x<4,5
uwzględniając zał. mamy: x∈(1/2 ; 4,5)
4-3x=4³
-3x=64-4
-3x=60
x=-60/3
x=-20
zad2 log2(2x-1)<3 zał: 2x-1>0→2x>1→x>1/2
2x-1<2³
2x<8+1
2x<9
x<4,5
uwzględniając zał. mamy: x∈(1/2 ; 4,5)
z.1
log4(4-3x) = 3
4^3 = 4 - 3x
64 = 4 - 3x
-3x = 63 -4 = 60
x = 60 :(-3 ) = - 20
odp. x = -20
z.2
log 2(2x -1) < 3
Rozwiążmy najpierw równanie log2(2x -1 ) = 3
2^3 = 2x - 1
8 = 2x - 1
2x - 1 = 8
2x = 8 + 1
2x = 9
x = 4,5
Odp. x < 4,5
log4(4-3x) = 3
4^3 = 4 - 3x
64 = 4 - 3x
-3x = 63 -4 = 60
x = 60 :(-3 ) = - 20
odp. x = -20
z.2
log 2(2x -1) < 3
Rozwiążmy najpierw równanie log2(2x -1 ) = 3
2^3 = 2x - 1
8 = 2x - 1
2x - 1 = 8
2x = 8 + 1
2x = 9
x = 4,5
Odp. x < 4,5